The sorrowful Muslim's guide - Amīn, Ḥusayn Aḥmad (In translation, modern Muslim thinkers., 2018)
Published as Dalil al-Muslim al-hazan ila muqtada-l-suluk fi'l-qarn al-'ishrin in 1983, this book remains a timely and important read today. Both the resurgence of Islamist politics and the political, social and intellectual upheaval which accompanied the Arab Spring challenge us to re-examine the interaction between the pre-modern Islamic tradition and modern supporters of continuity, reform and change in Muslim communities. This book does exactly that, raising questions regarding issues about which other Muslim intellectuals and thinkers have been silent. These include - among others - current religious practice vs the Islamic ideal; the many additions to the original revelation; the veracity of the Prophet's biography and his sayings; the development of Sufism; and historical and ideological influences on Islamic thought.